2012
DOI: 10.1093/infdis/jis536
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Surveillance Among Children With Pneumonia Admitted to a District Hospital in Coastal Kenya, 2007–2010

Abstract: Background. Influenza data gaps in sub-Saharan Africa include incidence, case fatality, seasonal patterns, and associations with prevalent disorders.Methods. Nasopharyngeal samples from children aged <12 years who were admitted to Kilifi District Hospital during 2007–2010 with severe or very severe pneumonia and resided in the local demographic surveillance system were screened for influenza A, B, and C viruses by molecular methods. Outpatient children provided comparative data.Results. Of 2002 admissions, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…The cross‐sectional study design has limitations. Data were collected during the rainy season, and pneumonia cases peak from January to March, possibly inflating the point prevalence of ARI. The period prevalence should not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…The cross‐sectional study design has limitations. Data were collected during the rainy season, and pneumonia cases peak from January to March, possibly inflating the point prevalence of ARI. The period prevalence should not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese longitudinal study of 190 ICV isolates collected over seven years found that nearly all were <6 years old, with the highest rates of infection in children 1-2 years old [60]. Rates of detection of ICV in outpatient or hospitalized children with acute respiratory illness have ranged from 0.7-10% in studies from Australia, Canada, Cuba, India, Italy, Japan, Nigeria, Peru, Scotland, and Spain [1,12,20,61,63,68,70,[91][92][93][94][95][96][97][98][99][100][101][102]. Most of these studies found higher rates of ICV infection in younger children.…”
Section: Icv In Childrenmentioning
confidence: 99%
“…Most of these studies found higher rates of ICV infection in younger children. Several studies have reported ICV as a cause of radiographic pneumonia in children, in some series as frequently as IBV [92,95,102]. These widely varied rates are likely due to varying circulation of ICV in different years; several studies have reported large outbreaks in a single year [61,94,98,99].…”
Section: Icv In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In Kenya, a country of 44 million people with a tropical climate and a per capita gross domestic product of $1800 in 2012, 6 recent studies have shown that influenza circulates year-round and the incidence of influenza is at least as high as it is in other parts of the world and particularly high in children <2 years old. 7,8 Influenza vaccine is not provided by the government, and <45,000 doses of influenza vaccine are purchased privately every year. A recent study found that Kenyans were aware of the seasonal influenza, although they were not aware of seasonal influenza vaccine.…”
mentioning
confidence: 99%